Cost-Effectiveness Analysis of Gemtuzumab Ozogamicin for First-Line Treatment of Patients with Cd-33 Positive Acute Myeloid Leukaemia in Spain [Corrigendum] - Mareque M; Montesinos P; Font P; Guinea JM; de la Fuente A; Soto J; Oyagüez I; Brockbank J; Iglesias T; Llinares J; Sierra J (Dove Medical Press, 2021)
Mareque M, Montesinos P, Font P, et al. Clinicoecon Outcomes Res. 2021;13:263–277. Page 271, Results, Base Case, second line from the bottom, the text “€ 15,134” should read “€ 151,434”. The authors apologize for this error. Read the original article